Impacts of climate change on shipping and business continuity management - Pang, Qi Jun (2012)
Climate change poses risks to operations of the shipping industry, which includes both shipping companies and ports. Adapting to maritime disruptions to operations via enhancing operational resilience, rather than mitigating the cause of climate change, is the focus of this research. Solutions suggested by literature review are effective risk management, collaboration between supplier-customer and business continuity management. Face-to-face interviews and survey with managers and senior executives from container terminals and shipping companies were utilised for obtaining current risk management practices and alignment policies and assessment of its effectiveness. Primary data collection spanned preliminary study, investigative study and validation. Overall response rate attained was 13%. Qualitative research shows implementing collaborative business continuity management with supply chain partners would enhance operational resilience. A set of holistic business continuity guidelines, customised for the service-oriented shipping industry, is proposed and validated by industry experts. Some key components of the guidelines are joint risk analysis, collaboration on risk reduction methods based on the common risks, clear communications and information sharing between all parties for coordinated actions, adequate training of all relevant staff in executing tasks as assigned in business continuity plan and conducting drills in regular intervals. The key challenges to efficacy of the proposed guidelines are the feasibility and willingness to share sensitive information, with supply chain partners for collaboration and the costs involved in implementing business continuity policies. Close partnership between partners, amounting to affiliation, is recommended for collaborative business continuity management to succeed.